Clinician knowledge, clinician barriers, and perceived parental barriers regarding human papillomavirus vaccination: Association with initiation and completion rates. Issue 1 (3rd January 2017) - Rutten, Lila J. Finney; St. Sauver, Jennifer L.; Beebe, Timothy J.; Wilson, Patrick M.; Jacobson, Debra J.; Fan, Chun; Breitkopf, Carmen Radecki; Vadaparampil, Susan T.; Jacobson, Robert M.
Highlights: Clinician knowledge of HPV was high with some gaps in knowledge observed. Greater clinician knowledge and HPV vaccine initiation/completion are associated. Clinician barriers to HPV vaccination: safety, discussing sexuality, patient burden. Perceived parental barriers and site-level HPV initiation/completion are associated. Abstract: Purpose: We tested the hypothesis that clinician knowledge, clinician barriers, and perceived parental barriers relevant to the human papillomavirus (HPV) vaccination account for the variation in vaccine delivery at the practice-site level. Methods: We conducted a survey from October 2015 through January 2016 among primary care clinicians (n = 280) in a 27-county geographic region to assess clinician knowledge, clinician barriers, and perceived parental barriers regarding HPV vaccination. Primary care clinicians included family medicine physicians, general pediatricians, and family and pediatric nurse-practitioners. We also used the Rochester Epidemiology Project to measure HPV vaccination delivery. Specifically we used administrative data to measure receipt of at least one valid HPV vaccine dose (initiation) and receipt of three valid HPV vaccine doses (completion) among 9–18 year old patients residing in the same 27-county geographic region. We assessed associations of clinician survey data with variation in vaccine delivery at the clinical site using administrative data on patients aged 9–18 years (n = 68, 272). Results: Consistent with our hypothesis, we found that greater knowledge of HPV and the HPV vaccination was associated with higher rates of HPV vaccination initiation (Incidence rate ratio [IRR] = 1.05) and completion of three doses (IRR = 1.28). We also found support for the hypothesis that greater perceived parental barriers to the HPV vaccination were associated with lower rates of initiation (IRR = 0.94) and completion (IRR = 0.90). These IRRs were statistically significant even after adjustment for site-level characteristics including percent white, percent female, percent ages 9–13, and percent with government insurance or self-pay at each site. Conclusions: Clinician knowledge and their report of the frequency of experiencing parental barriers are associated with HPV vaccine delivery rates—initiation and completion. Higher measures of knowledge correlated with higher rates. Fewer perceived occurrences of parental barriers correlated with lower rates. These data can guide efforts to improve HPV vaccine delivery in clinical settings.